Mobile breathers in a Nonlinear model for DNA breathing - Gutierrez, Hernan Cortez; Filho, Elso Drigo; Ruggiero, José Roberto; Gutierrez, Milton Cortez (Eclética Química, 2017)
Objectives. Analyze the DNA dynamics in Peyrard-Bishop-Dauxois model (PBD) with different control parameters using its energy center of the mobile “breather”. Materials and methods. We used the Peyrard-Bishop-Dauxois mathematical model and the MATLAB software for studying the DNA dynamic using Morse potential, Symmetric Morse and the “hump” potential for simulating the interactions which arise the pile up. Results. It has been observed that the analytical and computational methods allow to detect the influence of the potentials of the PBD model in the behavior of the energy center in the presence of a couple of base A(adenine) or T(thymine) using the control of parameter α=-0.30 and velocity of mobile breather: v0=0.1. In the case of Morse potential, the center of energy respect to the mobile breather undergoes a change in its trajectory and produce a DNA breathing. Conclusions. Analytical and computational approaches can be used for obtaining differences respect to the DNA dynamics using different control parameters: velocity of BM and inhomogeneity. The potential “hump” may decrease the reflective effect with the indicated parameters to the effect on the energy center to the mobile breather.